Social processes in academic-community partnership in health care. A grounded theory study - Susanna Pusa; Susanne Lind; Marie Häggström (BMC, 2021)
Abstract Background International and national guidelines state that palliative care should be offered to everyone who needs it. To promote the implementation of palliative care in nursing homes, a partnership collaboration was initiated with the goal of implementing high quality palliative care. The partnership consisted of three partner groups: a project group from a non-profit organisation providing health care, managers at the nursing homes and an academic partner. The aim was to explore the social processes within academic-community partnership in a collaboration project. Methods Digital focus group discussions were conducted with 16 participants, representing all three partner groups. One individual digital interview was also carried out. A constructivist perspective of a grounded theory approach was used for data analysis. Results The core category, partnership positioning, covers the social processes of the academic-community partnership in a collaboration project to implement and evaluate health-promoting interventions in clinical health care. The core category was found to have four categories: Pre-positioning, Co-positioning, Re-positioning and GoOn-positioning. The process of partnership positioning is conceptualised in a model. Conclusions Our findings indicate that a new partnership in an implementation project needs holistic, systemic thinking. To enhance implementation in a collaborative project involving different professionals and actors a plan is required to facilitate positioning activities. The process, the roles and the components need to be clearly defined and documented, and the management of a system requires knowledge of the interrelationships between all the components within the system. The development of a conceptual model of Partnership Positioning contributes to knowledge concerning the social dynamic processes which can be applied to support future academic-community collaboration and/or implementation projects. Trial registration Not applicable. The present study has not been considered as a clinical trial.